Fourier series of functions with infinite discontinuities - Sarić, Branko (Sarajevo Journal of Mathematics, 2024)
Using the total H_1-integrability concept we shall show that functions, which take on infinite values in the interval ( -π ,π ) at only finitely many places, can be expanded into a Fourier series over this interval.